Analysis of the Relationship between Telecommuting with Work-Life Balance and Job Satisfaction (Meta-Analysis Study) - Riki Setiawan; Endang Siti Astuti; Kusdi Raharjo (Sekolah Pascasarjana Universitas Brawijaya, 2022)
This study examines and analyzes the relationship between telecommuting with work-life balance and job satisfaction. The data analysis technique used in this study is meta-analysis correlation—used to see the relationship between two variables by utilizing the results of previous correlation studies, which consist of two main components: calculating the effect size and summary effect. The number of studies used as relevant data in the study was 18 journals containing 26 statistical data used as material for data analysis. The data is processed using a statistical tool, JASP software version 0.14.1 2020. The results show that telecommuting can increase work-life balance and job satisfaction for members of the organization that runs it, as well as the work-life balance, which can create a strong relationship with job satisfaction in the context of implementing telecommuting. Keywords: telecommuting, work-life balance, job satisfaction, meta-analysis